Turbulence Properties of a Deep‐Sea Hydrothermal Plume in a Time‐Variable Cross‐Flow: Field and Model Comparisons for Dante in the Main Endeavour Field. Issue 9 (15th September 2021) - Adams, Ian; Di Iorio, Daniela
Abstract: A large eddy simulation is used to study a high temperature hydrothermal vent plume in a stratified and tidally modulated crossflow, in order to identify its turbulence and mixing characteristics. The model parameters and source conditions that are comparable to the vertical velocity and refractive index fluctuations measured 20 m above the Dante sulfide mound in the Main Endeavour vent Field are a heat transport of 50 MW over a cross‐sectional area of 4 × 4.5 m 2 . With these model source conditions and output results taken at 20 m above the source with 1 Hz sampling, the shear production of turbulent kinetic energy (TKE), the vertical transport of TKE, and the buoyancy production/dissipation are quantified showing that shear production dominates. Similarly, thermal variance production, and its vertical transport, is also quantified showing that the advective term dominates. Because of enhanced entrainment of ambient water into the plume during strong crossflows, all mean and turbulent quantities show tidally modulated values. Assuming steady state, the dissipation rates are evaluated. During strong crossflows, the tilting of the vertical velocity contours and isotherms plays a critical role in the stability of the plume and in creating high shear and thermal gradients on the upstream side of the plume center axis. These dissipation rates are used to quantify the refractive index fluctuations, and given the high thermal dissipation quantity it is the main contributing factor in acoustic forward scatter. Plain Language Summary: At mid‐ocean ridges, magma‐heated fluid, flows out of cracks in the crust, releasing high levels of heat and chemicals into the deep ocean in the form of hydrothermal plumes. Because of its buoyancy, the fluid quickly rises forming a turbulent convective plume entraining ambient seawater thus creating a transport mechanism into the deep ocean. Ocean currents complicate the rise of the buoyant plume, limiting its rise height by enhancing the amount of ambient water entrained into the plume and resulting in tidally modulated vertical velocities, turbulent properties, and rise heights. Modeling these systems leads to a better understanding of the mixing strengths within the plume and the rates at which turbulent kinetic energy (TKE) and temperature variations are produced and dissipated. These quantities are almost impossible to measure in a deep‐sea hydrothermal vent environment. Results show that shear is the primary mechanism for producing TKE and that the advection of temperature variability by the mean and turbulent vertical velocity is the primary mechanism for producing temperature fluctuations at 20 m above the vent orifice. Key Points: Shear production of turbulent kinetic energy is balanced by dissipation For thermal variance, the vertical transport and its flux divergence balance the dissipation Hydrothermal discharge at the Dante sulfide mound modeled with a heat transport of 50 MW over a 4 × 4.5 m 2 area is comparable to observations